KNOWLEDGE CONSTRUCTED IN THE PROJECT OF INCLUSION IN ACADEMIC EXTENSION AT FEEVALE/RS (Fiep Bulletin - online, 2014)
Abstract: This article approaches the knowledge constructed and the importance of academic extension in a Physical Education Course inclusion project entitled: Aquatic Activities, Sports and Wrestling for PNEs (National Extension Plans), "Physical Activities and Inclusive Sport". The general aim of the project is to make the inclusion of PNEs in different sports and leisure activities possible and to promote an academic learning in the academic extension program. The practices are developed through weekly meetings where the participants experience their activities oriented by teachers and Physical Education trainees from Centro Universitário Feevale. As results for the project we can mention: assistance to people historically excluded from these activities; production of new knowledge about inclusion; and training of academic formation of teachers and future teachers in the inclusion field.
Keywords: Inclusion; People with Special Needs; Professional Formation